Imagens veladas no cinema de Wong Kar-Wai - Boff, Fernanda Vieira (Universidade do Vale do Rio dos Sinos, 2011)
A study on the potentialities of the elements that are veiled in the image of the films In the mood for love (2000) and Fallen Angels (1995) directed by Wong Kar-wai. This matter is analyzed through a focused look through the frame, composition, framework, deframing, and the bright and dark zones in the films. The objective of the analysis is to discuss how the use of these elements can enrich the content of the narrative. These concepts are elucidated with the analysis of the scenes and the use of some frames of the films, aiming to reflect about what is denied and what is potentially revealed to the spectator. The bibliography is based on Jacques Aumont and on concepts of movie and image proposed by different authors such as René Gardies, David Bordwell, Didi-Huberman, Gilles Deleuze e Francisco Javier Gómez Tarín.
Keywords: Cinema; Imagem; Enquadramento; Fora-de-campo; Direção de fotografia; Image; Framing; Offscreen; Direction of photography